The effect of implanting beef heifers on a fattening ration with hormones or hormone-like substances - Richardson, D.; Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
The increase in rate of gain from feeding stilbestrol to heifers is not so good as that obtained with steers. Implanting heifers with levels of stilbestrol recommended for steers results in undesirable side effects such as udder and teat development, high tailheads, and prolapse of the vagina in many instances. This is the second test designed to study the effect of low-level stilbestrol implanting (12 mgs.) and Synovex heifer implants (SH-7 contains 100 mgs. testosterone and 20 mgs. estradiol benzoate) on heifers being fattened for slaughter. Sixty heifers, six lots of 10 animals each, in Projects 536 and 537 were used in this test. Three animals from each lot were randomly selected to receive either the stilbestrol or Synovex implant, thus giving 18 animals per treatment. The remaining 4 animals per lot, total of 24, served as controls.
Keywords: Beef; Implant; Ration; Hormones